RASIO BELANJA LANGSUNG DAN TIDAK LANGSUNG TERHADAP TOTAL BELANJA PROVINSI SULAWESI TENGGARA TAHUN 2017 - 2021 - Rahmat Hidayat; Runi Paga’ga’; Ningsi (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2022)
ABSTRACT This study aims to calculate the Influence of Direct and Indirect Expenditures on Total Expenditures in Southeast Sulawesi. The indirect spending ratio in 2017 was 22.85% and the direct spending ratio was 77.14%, indicating that direct spending in 2017 was greater than indirect spending. Not only in 2017, in 2018 direct spending was bigger than indirect spending. In the last four years (2017-2020) the ratio of indirect spending has increased every year, but in 2021 the ratio of indirect spending has decreased by 10.92%. This is inversely proportional to the direct expenditure ratio, which in the last four years (2017-2020) has decreased every year. However, in 2021 the direct expenditure ratio will increase by 10.92% from the previous year (2020). This shows that the government has paid attention to improving the quality of output, so that the function of the budget as a distribution, allocation and stabilization tool can work well. Keywords : Live Shopping, Shopping Not Directly, Total Martial arts.